“I CAN STRIVE FOR EXCELLENCE AND STILL BE KIND TO MYSELF”: A CASE REPORT ON MULTIFACETED INTERVENTION FOR A YOUNG WOMAN WITH DEPRESSION AND OBSESSIVE-COMPULSIVE PERSONALITY TRAITS - Lee Sook Huey; Saw Jo Anne; Fatanah Ramlee, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Limited literature exists on the management of depression with comorbid Obsessive-Compulsive Personality Disorder (OCPD). This case report presents the psychological intervention provided for a young woman with clinical depression, anxiety, and traits of OCPD. Additionally, she exhibits distinctive maladaptive coping mechanisms, having created vivid characters in her mind since a young age to ensure flawless behaviors. The treatment approach was based on the framework of cognitive behavioral therapy and incorporated elements of compassion training and dialectical skills training. The intervention aimed to address the complex interplay between depression, anxiety, OCPD traits, and the unique coping strategies observed in the patient. As a result of the treatment, her BDI score reduced from severe to mild, and she demonstrated an increase in healthy coping skills. This case report documents the treatment approach used to address the multidimensional challenges presented by individuals with comorbid conditions involving OCPD traits. Furthermore, recommendations are provided on how to manage similar cases.